37 With my family i have to think about them… with the girls [friends] i don't: the role of friendships in advance care planning. Issue 3 (1st September 2017) - Russell, Sarah
Abstract : Introduction: The role of friendships is under-reported in the research literature despite evidence that advance care planning is both a social experience and a health care decision making one. Aim/Method: As part of a doctoral study, the influences on advance care planning was explored using a qualitative narrative approach to 15 indepth interviews; analysed by a data driven thematic analysis method. Results: One finding was the influence of friendships on advance care planning; forums for discussion, entertainment, diversion, practical support, reality checks and 'safe' spaces for discussions/decisions about preparing and planning for dying unencumbered by concerns for the emotional well being of informal carers, family or children. Participants retained their identity as a 'person' rather than a dying patient supporting them to live with the knowledge of their future death. Conclusion: The importance of friendships at the end of life (Cartwright and Seale 1990) and influence of social networks is described in the literature (Leonard et al 2015), especially in terms of formal and informal support (Lewis et al 2014). However, the role of friendships is often under reported because dying is seen primarily as a family event or difficult to define (de Vries and Johnson 2002). If death is both a health and social experience (Sudnow 1967) then the social elements of dying (e.g friendships) should not be subsumed by the biomedical focus of palliative care (Lewis et al 2013). The findings from this study provides practical insights into the role and definitions of friendships in advance care planning and end of life. References: . Cartwright A and Seale C (1990) The natural history of a survey:an account of methodological issues encountered in a study of life before death. King Edwrds Hospital Fund for London. . de Vries B and Johnson C (2002) The death of friends in later life. Advances in life course research7:299–324 . Leonard R, Horsfall D, Noonan K (2015) Identifying changes in the support networks of end of life carers using socia network analysis. BMJ Supportive and Palliative Care 5(2):153–159. . Lewis JM, DiGiacomo M Currow DC, Davidson PM (2013) A Social Capital Framework for Palliative Care: Supporting Health and Well Being for People with Life Limiting Illness and their Carers through Social Relations and Networks. Journal of Pain and Symptom Management45(1):92–103 . Sudnow D (1967) Passing On. Prentice Hall.